Sistem Informasi Pendaftaran Pasien Secara Online Pada Puskesmas Citeureup - Duwi Cahya Putri Buani; Stefanus Yogi Gunawan (LPPM Universitas Bina Sarana Informatika, 2022)
The patient registration process at the Citeureup Health Center is still carried out manually where patients have to come directly and queue when they want to seek treatment at the Puskesmas, sometimes experience long queues during registration, and it is difficult to find service information or news about Citeureup Health Center. From these problems, the Citeureup Health Center requires an online patient registration information system. The online patient registration information system at the Citeureup health center is designed using the Waterfall method, the Waterfall method is a method that is very easy to follow every step of the way and is suitable for designing an online patient registration system. The results of this study are an online patient registration information system and information/news about the Citeureup Health Center, which is expected to help the Puskesmas, especially in the health service section, in serving patient registration and information to be provided to the public